2013
DOI: 10.1155/2013/201857
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Yang-Deficient Constitution and Clinical Outcome of Highly Active Antiretroviral Therapy on People Living with HIV

Abstract: Objective. To determine the association between Yang-Deficient Constitution and the clinical outcomes of HIV/AIDS patients who have initiated highly active antiretroviral therapy (HAART). Method. A total of 197 antiretroviral-naive adults who initiated HAART between 2009 and 2011 were recruited. The participants were asked to complete a questionnaire twice to assess their Yang-Deficient Constitution status before HAART. During the study, signs and symptoms and CD4 or CD8 T cell counts were recorded. Routine bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Same as previous report [4, 16], this study confirmed that male patients were less likely to be Yang-deficiency BC or blood-stasis BC in IgA nephropathy; this is consistent with TCM theory. In the “Yin-Yang” theory of TCM, the male is characterized by “Yang”, while the female is characterized by “Yin”.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Same as previous report [4, 16], this study confirmed that male patients were less likely to be Yang-deficiency BC or blood-stasis BC in IgA nephropathy; this is consistent with TCM theory. In the “Yin-Yang” theory of TCM, the male is characterized by “Yang”, while the female is characterized by “Yin”.…”
Section: Discussionsupporting
confidence: 92%
“…The Constitution in Chinese Medicine Questionnaire (CCMQ), issued by the China association of TCM in 2009, was adopted to evaluate the participants' BC statuses [4].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, patients with breast cancer and different TCM constitutions may have different degrees of myelosuppression after chemotherapy [17]. Some studies have revealed that some constitutions may become predictive factors for death and morbidity of some diseases [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is not known how the slowdown in CD4 T cell decline is related to the course. Bioinformatics techniques were used to explore patterns in various settings [11][12][13][14][15] and an in-depth pattern discovery shall shed light for better design of molecular experiments, drug administration and policy making.…”
Section: Introductionmentioning
confidence: 99%